Penerapan Keadilan Restoratif bagi Penyalahguna Narkotika: Studi Kasus di Kejaksaan Negeri Takalar - Resky Ayu Lestari; Syarif Saddam Rivanie; Slamet Sampurno Soewondo (SIGn Jurnal Hukum, 2023)
This research aims to examine and analyze how the Takalar Public Attorney’s Office applies the Guidelines of Attorney General Number 18 of 2021. This research uses an empirical legal research method. All collected data is then qualitatively analyzed to describe the problem and answer the research objectives. The results show that Sofyan Setiawan’s case is the sole example of implementing restorative justice, aligning with the Guidelines of Attorney General Number 18 of 2021 at the Takalar Public Attorney’s Office. The entire legal process, from the drafting of the legal opinion by the Public Prosecutor to the issuance of Letter Number B-230/P.4.32/Es.1/08/2022 by the Head of the Takalar Public Attorney’s Office, demonstrates compliance with formal and material completeness. Instructions for resolving the case were subsequently forwarded to the High Attorney’s Office of South Sulawesi. The progression to restorative justice was documented in Letter Number R-/P.4.4/Enz.1/08/2022, issued by the Assistant for General Crimes on behalf of the Head of the High Attorney’s Office of South Sulawesi. Sofyan Setiawan then effectively underwent rehabilitation from August 3 to December 3, 2022, at the Baddoka Narcotic Rehabilitation Center in Makassar. Therefore, several recommendations can be proposed to the relevant stakeholders. First, the Head of the Takalar Public Attorney’s Office and the High Attorney’s Office of South Sulawesi should collaborate to identify the formal and material completeness criteria enabling broader implementation of restorative justice. Second, the Assistant for General Crimes and the Public Prosecutor are advised to develop a systematic evaluation mechanism to assess the effectiveness of rehabilitation as one of the options for resolving narcotic criminal cases. Third, the Baddoka Narcotic Rehabilitation Center in Makassar and relevant institutions in Makassar are recommended to enhance the capacity of their facilities and rehabilitation services, especially considering the high number of narcotic cases. These measures aim to improve the effectiveness and scope of restorative justice in handling similar cases in the future.